Dryland Grain Sorghum in Southeast Kansas - Fausett, Marvin R. (My University, 1995)
This publication outlines the expected costs and returns for dryland grain sorghum production in southeast Kansas.
MF995_1995_10
Keywords: MF995; Economics; Crops; MF